(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
TITLE Core strength training’s impact on badminton players’ performance skills is compared before andafter.BACKGROUND Reduced core muscle strength is an independent risk factor for sports injury and injuryin badminton players. Core stability depends on core strength, which also lowers injury risk andimproves performance.PURPOSE OF STUDY The goal is to evaluate how a core-strengthening exercise programme affectsplayers’ performance abilities and core stability.METHODOLOGY In this study 30 badminton players were included for the study, pre and postintervention assessment was done for strength using outcome measure (Lockhart-Mcphersonbadminton test and Miller Wall-Volley test) followed by core strengthening exercises programme toperform 45 mins for 5 days per week for 6 weeksRESULT According to table 1, Graph 1, Graph 2 training in core strength has shown that Lockhart-Mcpherson badminton test score increases in mean value from 116.03 to 124 between pre and post-testand Miller Wall-volley in mean value from 102.82 to 111.56.The table infers a significant increase in Lockhart-Mcpherson badminton test and Miller Wall-volley testscore by core strength training at P < 0.05.CONCLUSION The result indicates that core strength training programme are significantly effective inimprovement of core stability performance skills in badminton players